Topics in the routine assessment of newborn kitten vitality: Apgar score, reflexes and complementary assessments - Hibaru, Viviane Yukari [UNESP]; Pereira, Keylla Helena Nobre Pacífico [UNESP]; Fuchs, Kárita da Mata [UNESP]; Lopes, Maria Denise [UNESP]; Alfonso, Angélica [UNESP]; de Souza, Fabiana Ferreira [UNESP]; Chiacchio, Simone Biagio [UNESP]; Tsunemi, Miriam Harumi [UNESP]; Machado, Luiz Henrique de Araújo [UNESP]; Lourenço, Maria Lucia Gomes [UNESP] (SAGE Publications, 2022)
Objectives: The aim of this study was to perform neonatal clinical assessments at birth to identify newborn kittens at risk according to type of delivery, thus allowing immediate intervention and increasing their chances of survival. Methods: This study compared Apgar scores, reflexes and clinical parameters (temperature, weight, blood glucose and peripheral oxygen saturation [SpO2]) between eutocic neonates and those delivered by emergency cesarean section. The animals were evaluated at birth and after 10 and 60 mins. Results: Thirty-two neonates were evaluated, with 19 animals in the eutocic group (EG) and 13 animals in the cesarean group (CG). When comparing groups, CG neonates had significantly lower Apgar scores (P <0.0001), lower SpO2 (P = 0.0535), higher blood glucose (P = 0.0009), reduced reflexes (P <0.0001) and lower respiratory rates (P <0.0001) at birth and after 10 and 60 mins than EG neonates. Apgar scores positively correlated with parameters such as heart rate, reflex score, SpO2 and weight. The mortality rate in evaluated newborns was 15.6% (5/32). The early mortality rate (0–2 days old) was 80% (4/5) and the late mortality rate (3–30 days old) was 20% (1/5). Conclusions and relevance: This study showed lower vitality in cats delivered by emergency cesarean section than in those delivered through eutocic birth. In general, neonates delivered by cesarean section have greater depression and low vitality at birth and may require advanced resuscitation procedures. The evaluations carried out in this study identified newborns with low vitality and those requiring advanced resuscitation, thus allowing immediate intervention. Apgar and reflex scores for feline neonates were suggested. Newborn-specific clinical assessment with these feline vitality scores allows the identification of at-risk neonates. Care immediately after birth increases the chance of survival among these patients.
Keywords: Apgar score; cats; cesarean section; Feline neonate; mortality